DOI: 10.11606/t.106.2015.tde-17072015-213348
|View full text |Cite
|
Sign up to set email alerts
|

Integração das políticas públicas de recursos hídricos e saneamento: a bacia hidrográfica dos Rios Sorocaba e médio Tietê

Abstract: AGRADECIMENTOS Agradecimentos especiaisDou graças ao meu Pai Celestial, quem me abriu tantas portas, me possibilitou trabalhar com aquilo que amo e aprender e contar com pessoas maravilhosas neste processo intenso e tão especial em minha vida. E também, porque me carregou em Seu colo em muitos momentos! Thiago, meu amado marido, eu sou grata por ter você em minha vida! Obrigada por sempre me apoiar e cuidar tão bem de mim e do Samuel. Obrigada pela compreensão, revisões de texto e pelos desenhos que elaborou p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…Just as in other studies (PAZ & JACOBI, 2015;PITERMAN;HELLER & REZENDE, 2013), it was observed that public basic sanitation services are still not discussed in CMPU meetings, even in delicate moments for the are in the Municipality, with the rotation system in water supply. The existence of this instance for social control was not enough for such control to happen.…”
Section: Chart 1 Bodies Represented In the Council According To Segmmentioning
confidence: 77%
See 3 more Smart Citations
“…Just as in other studies (PAZ & JACOBI, 2015;PITERMAN;HELLER & REZENDE, 2013), it was observed that public basic sanitation services are still not discussed in CMPU meetings, even in delicate moments for the are in the Municipality, with the rotation system in water supply. The existence of this instance for social control was not enough for such control to happen.…”
Section: Chart 1 Bodies Represented In the Council According To Segmmentioning
confidence: 77%
“…The Decree to close it was issued in March 28, 2018 by the mayor, and its effective closure happened in June 2018. The way this Council attribution was instituted and the councilors' answers showed that this policy was imposed, a characteristic top-down policy for a PI that, at that moment, or due to the way it was imposed, did not present the propensity to deal with basic sanitation issues, even though many authors observe the relation between development and urban policy and the basic sanitation area (HELLER, 2015;PAZ & JACOBI, 2015;PITERMAN;HELLER & REZENDE, 2013). That is also seen among interviewees, who mention the centralizing discourse as the main obstacle for the Council to fulfill its attribution of a social control organ.…”
Section: Chart 1 Bodies Represented In the Council According To Segmmentioning
confidence: 99%
See 2 more Smart Citations
“…Tanto no world café, quanto no espaço aberto, o objetivo concentrava-se em criar um ambiente confortável e informal para o diálogo (BROWN, 2001;CAMARGO, 2011;OSDE, 2006 De acordo com Paz et al (2014 , p. 1), os atores evidenciaram a relação saneamento-saúde com falas, tais como: "saneamento básico é importante para evitar doença"; "água tratada é sinônimo de saúde"; e "O meio mais prático para a saúde, é o saneamento chegar junto com a rede de em 2007em , pela lei 11.455 (BRASIL, 1999. Por meio do controle social, é possível assegurar a participação popular na prestação de serviços de saneamento, conferindo, à gestão em exercício, importantes características, tais como a transparência, o comprometimento com as demandas da sociedade, além de ampliação de perspectivas de prestação de serviços (JACOBI, 2000(JACOBI, , 2003(JACOBI, , 2004PAZ, 2014;BEDUSCHI FILHO, 2007). Para que os serviços públicos de saneamento básico sejam ofertados aos usuários com qualidade, de maneira integral e universal, deveriam alavancar a participação e o controle social como condição fundamental no saneamento e na gestão hídrica.…”
Section: O Impacto Dos Métodos Participativosunclassified